Revisiting a classic: James Burney and A History of the buccaneers of America. A definitions of the world at the beginning of the 19th century (2012)
Taking into consideration literature and history, together with the accounts of the English naval officer James Burney, this paper examines the 18th century's knowledge-acquisition process regarding ocean navigation and makes special emphasis on the journeys in the Caribbean.